BELLIGERATIVE PROPERTIES OF RELIEF - Стецюк, В.; Ковальчук, І. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The role of the Earth's surface topography and its performance characteristics as the factors that affect significantly the placement and operation of military facilities, conducting offensive and defensive warfare have been described. The expediency of using geomorphological methods, GIS and remote sensing data in the evaluation of potential belligerative relief and it creation, and geomorphological processes, threats and risks to infrastructure and military activities have been reviewed. Keywords: relief, geomorphological processes, belligerative properties of relief, geomorphological risks and threats.